Does nest placement in buildings influence nest predation in red-billed choughs?. Issue 5 (3rd September 2017) - Banda, Eva; Blanco, Guillermo
Abstract : Factors determining nest predation are often multiple and spatiotemporally variable. We evaluated the relative importance of nest placement on predation risk of red-billed choughs ( Pyrrhocorax pyrrhocorax ) nesting in abandoned buildings in north-eastern Spain, while controlling for other potentially influential social, population and landscape variables at several spatial scales. Data from 705 breeding attempts belonging to 405 different pairs nesting in 342 different buildings were obtained in three breeding seasons. Nest predation was the main cause of reproductive failure. Breeding density at the territory scale and laying date were the variables most influential on nest predation. No single or combined predictors of nest predation were identified among the variables describing nesting buildings and nest placement within them. The dereliction status of buildings and the bulky and accessible nature of chough nests may result in a lack of a general pattern of nest placement that explains nest predation by the entire predator guild. Specific features of nest microhabitat explaining predation rates by particular predator species would require further research associating specific predators with the nests on which they prey, after controlling for the influence of incidental predation.